Health Effects of Probiotics on Nonalcoholic Fatty Liver in the Life Cycle Based on Data Analysis. (29th July 2022) - Wang, Jia; Hao, Yanfei; Jin, Xiao; Li, Xiaoyue; Liu, Yi; Zhang, Li; Wang, Jing; Hu, Mingxin
Abstract : Objective . To observe the effect of intestinal probiotics in the treatment of nonalcoholic fatty liver disease (NAFLD) and the effect on liver function and inflammatory factors. Methods . 34 healthy rats were selected for the study and divided into 10 rats in the control group, 12 rats in the model group, and 12 rats in the treatment group according to the random number table method. The control group was given behavioral and lifestyle interventions, and the treatment group was given Bifidobacterium minus Black enteric capsules 5 g/(kg-d) by strong feeding method on the basis of the control group. The fatty liver index (FLI), liver ultrasound examination results, liver function, and inflammatory factor levels were compared among the three groups. After 8 weeks of treatment, there were statistically significant differences between the FLI values and liver ultrasound results of the three groups, and the serum alanine aminotransferase (ALT), aspartate aminotransferase (AST), triacylglycerol (TG), and total cholesterol (TC) levels of the observation group were lower than those of the control group and the model group. The levels of serum high molecular weight lipocalin (HMW-APN) and interleukin 22 (IL-22) in the observation group were higher than those in the control group, and the levels of tumor necrosis factor- α (TNF- α ) were lower than those in the control and model groups, and the differences were statistically significant (P < 0.05 ). Conclusion . Intestinal probiotics can improve the clinical efficacy of patients with NAFLD, improve liver function, and alleviate the inflammatory response, in order to provide a theoretical basis for the clinical treatment of patients with NAFLD.